Fluid shear triggers microvilli formation via mechanosensitive activation of TRPV6 - Shigenori Miura; Koji Sato; Midori Kato‐Negishi; Tetsuhiko Teshima; Shoji Takeuchi (2015)
Microvilli are cellular membrane protrusions present on differentiated epithelial cells, which can sense and interact with the surrounding fluid environment. Biochemical and genetic approaches have identified a set of factors involved in microvilli formation; however, the underlying extrinsic regulatory mechanism of microvilli formation remains largely unknown. Here we demonstrate that fluid shear stress (FSS), an external mechanical cue, serves as a trigger for microvilli formation in human placental trophoblastic cells. We further reveal that the transient receptor potential, vanilloid family type-6 (TRPV6) calcium ion channel plays a critical role in flow-induced Ca(2+) influx and microvilli formation. TRPV6 regulates phosphorylation of Ezrin via a Ca(2+)-dependent phosphorylation of Akt; this molecular event is necessary for microvillar localization of Ezrin in response to FSS. Our findings provide molecular insight into the microvilli-mediated mechanoresponsive cellular functions, such as epithelial absorption, signal perception and mechanotransduction.